Videolaryngoscopy versus fiberoptic bronchoscope for awake intubation – a systematic review and meta-analysis of randomized controlled trials - Jiang J; Ma DX; Li B; Wu AS; Xue FS (Dove Medical Press, 2018)
Jia Jiang,1 Da-Xu Ma,1 Bo Li,2 An-Shi Wu,1 Fu-Shan Xue31Department of Anesthesiology, Beijing Chaoyang Hospital, Capital Medical University, Beijing 100020, China; 2Beijing Hospital of Traditional Chinese Medicine, Affiliated to Capital Medical University, Beijing Institute of Traditional Chinese Medicine, Beijing 100010, China; 3Department of Anesthesiology, Beijing Friendship Hospital, Capital Medical University, Beijing 100050, China Background: Awake intubation with videolaryngoscopy (VL) is a novel method that is drawing more and more attention as an alternative to awake intubation with fiberoptic bronchoscope (FOB). This meta-analysis is designed to determine the performance of VL compared to the FOB for awake intubation.Methods: The Cochrane Central Register of Controlled Trials, PubMed, Embase, and Web of science were searched from database inception until October 30, 2017. Randomized controlled trials comparing VL and FOB for awake intubation were selected. The primary outcome was the overall success rate. Rev-Man 5.3 software was used to perform the pooled analysis and assess the risk of bias for each eligible study. The GRADE system was used to assess the quality of evidence for all outcomes.Results: Six studies (446 patients) were included in the review for data extraction. Pooled analysis did not show any difference in the overall success rate by using VL and FOB (relative risk [RR], 1.00; P=0.99; high-quality evidence). There was no heterogeneity among studies (I2=0). Subgroup analyses showed no differences between two groups through nasal (RR, 1.00; P=1.00; high-quality evidence) and oral intubations (RR, 1.00; P=0.98; high-quality evidence). The intubation time was shorter by using VL than by using FOB (mean difference, -40.4 seconds; P<0.01; low-quality evidence). There were no differences between groups for other outcomes (P>0.05).Conclusion: For awake intubation, VL with a shorter intubation time is as effective and safe as FOB. VL may be a useful alternative to FOB.Keywords: airway management, awake intubation, videolaryngoscopy, fiberoptic bronchoscopy, randomized controlled clinical trials, outcomes